(untitled) (Voice: A Biannual & Bilingual Journal, 2025)
Purpose: This study investigates potential differences in digital media exposure between urban and rural youths in Lumbini Province, Nepal, and whether such differences exist in their long-term purchasing behaviour. Design/Methodology/Approach: A cross-sectional quantitative survey was conducted with 500 youths (250 urban, 250 rural) aged 18-45 using stratified random sampling. Data were collected through structured questionnaires (using a 5-point Likert scale; Cronbach’s α = 0.84) and analysed using descriptive statistics, independent samples t-tests, and linear regression. Findings/Result: While urban youths reported higher consistent usage ("always": 33.2% vs. 28.4%), urban youths and rural youths reported higher occasional usage ("sometimes": 36.8% vs. 28.4%). While the behaviour is different, there was no significant difference in the mean overall usage intention between groups (t-test, p = .376; regression, p = .260). Significant barriers limiting use in rural areas included connectivity gaps, the ability to access devices, and limited digital literacy. Originality/Value: This is the first provincial-level comparative study in Nepal exploring the roles of Pinterest and TikTok in rural decision-making. It provides a distinct attention on divides related to infrastructure and trust that do not rely on access stats, generating immediate interest for researchers and policymakers. Paper type: Research manuscript